Women faculty’s experiences with gendered microaggressions in science, technology, engineering, and mathematics - Yang, Yang; Carroll, Doris W. (Ohio Council of Professors of Educational Administration, 2018)
Women remain underrepresented in both science, technology, engineering, and mathematics (STEM) workforce and academia. In this quantitative study, we focused on female faculty across STEM disciplines and their experiences in higher educational institutions through the lens of microaggressions theory. Two questions were addressed: (a) whether and to what degree female faculty in STEM fields experience various types of gendered microaggressions and (b) whether such experience differ based on participants' position rankings. Data were collected from tenured (including tenure-track) and nontenure-track female instructional and clinical faculty in a broad range of STEM disciplines at a large Midwestern land grant research university (N = 102), using two adapted instruments. The results revealed that female faculty participants experienced four different types of gendered microaggressions: "sexual objectification," "being silenced and marginalized," "strong woman," and "workplace microaggressions." Multivariate analysis further showed that position ranking did not statistically predict faculty experiences with gendered microaggressions, indicating that gendered microaggressions were experienced by women faculty regardless of the stages of their faculty career. Implications and the need for future research are also discussed.
Keywords: women; faculty; gendered microaggressions; STEM career; higher education